Maintenance factor for precast concrete in IBS: A review - Ng, Ban Kiong; Akasah, Zainal Abidin (2011)
Industrialized Building System(IBS) is one of the construction method that utilized where the components are manufactured in factory or in-situ. Each components are produced in a controlled and monitored environment, transported and installed with minimum workforce. This system are widely used in Malaysia and commonly there are six types of IBS which known as precast concrete frame, formwork system, steel formwork system, steel frame system, prefabricated timber system, block work systems and other innovative system. But at the same time, when a building was built by the IBS system, there are lots of maintenance problem that affect the building operation and quality. Hence, the factor that affect the quality of the IBS building should be identify and find out the solution to overcome the problem. Thus, this study will focus on poor practicing in design stage, manufacturing stage and construction stage that affect the quality of the building which leads to building maintenance. The objective of this study is to identify the factors of defect during design, construction and manufacturing stage of precast concrete that affect the quality of the building, then identify factors that are related to poor maintenance consideration during design, manufacturing and construction stage and last but not least to recommend solutions to overcome problem. All the data collection will be done in the form of questionnaire and distributed to the contractors, consultants and manufacturers. The IBS building maintenance problem in civil and architectural will be collect after the feedback from the potential respondent and analysis through the Statistical Package for the Social Science (SPSS) and note down in a check list. Hopefully from the analysis, a crucial part of the factor that affect the quality of the precast concrete building will be identified and will be supported through the propose suggestion and solution that will reduce the cost and time of maintenance in IBS building which use the precast concrete method.